2010
DOI: 10.1007/s00415-010-5551-2
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 (PON1) polymorphisms and risk for migraine

Abstract: The polymorphic enzyme human serum paraoxonase 1 (PON1), encoded by the gene PON1 (chromosome 7q21.3) plays a role as an antioxidant molecule through several mechanisms. Because oxidative stress has been implicated in the pathogenesis of migraine, we have investigated the possible association between the nonsynonymous polymorphisms 55LM and 192QR in the PON1 and the risk for migraine. We studied the frequency of the PON1 genotypes and allelic variants in 197 patients with migraine and 220 healthy controls usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Recruitment of patients was done in the general neurological clinics of 3 University Hospitals during the period between September 2006 and August 2007 (the onset of migraine attacks was under age 15 years in 113 patients, positive family history for migraine was reported by 147 patients, and 98 of them had MWA). Most of these patients have participated previously in other genetic association studies reported by our group …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment of patients was done in the general neurological clinics of 3 University Hospitals during the period between September 2006 and August 2007 (the onset of migraine attacks was under age 15 years in 113 patients, positive family history for migraine was reported by 147 patients, and 98 of them had MWA). Most of these patients have participated previously in other genetic association studies reported by our group …”
Section: Methodsmentioning
confidence: 99%
“…Most of these patients have participated previously in other genetic association studies reported by our group. 3,[53][54][55][56][57][58] Control individuals were healthy Caucasian Spanish subjects recruited from professors or students from the University of Extremadura, who did not suffer from migraine or other headache types, and have not familial history of migraine. They were interviewed by three physicians (Drs.…”
Section: Methodsmentioning
confidence: 99%
“…All eligible patients were invited to participate and all of them agreed to do so. These patients participated in other genetic association studies by our group …”
Section: Methodsmentioning
confidence: 99%
“…These patients participated in other genetic association studies by our group. [24][25][26][27][28] Controls were healthy unrelated Caucasian Spanish individuals, most of them students or professors from the University of Extremadura, who did not have either personal or familial positive history of migraine and did not suffer from other headache types. Controls matching gender and age with patients in the study were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, PON1 concentrations and activity were reported to be better markers of cardiovascular diseases in comparison with PON1 genotype (8,19). García-Martín et al (23) reported an absence of a difference between patients with migraine and controls in terms of PON1 genotypes and allelic variants. Yıldırım et al (22) also reported similar results.…”
Section: Discussionmentioning
confidence: 99%